Diversity and assembly of root-associated microbiomes of rubber trees - Lan, Guoyu; Wei, Yaqing; Li, Yuwu; Wu, Zhixiang (Frontiers in Plant Science, 2023)
Introduction Understanding the diversity and assembly of the microbiomes of plant roots is crucial to manipulate them for sustainable ecosystem functioning. However, there are few reports about microbial communities at a continuous fine-scale of roots for rubber trees. Methods We investigate the structure, diversity, and assembly of bacterial and fungal communities for the soil (non-rhizosphere), rhizosphere, and rhizoplane as well as root endosphere of rubber trees using the amplicon sequencing of 16S ribosomal ribonucleic acid (rRNA) and Internally Transcribed Spacer (ITS) genes. Results We show that 18.69% of bacterial and 20.20% of fungal operational taxonomic units (OTUs) in the rhizoplane derived from the endosphere and 20.64% of bacterial and 20.60% of fungal OTUs from the soil. This suggests that the rhizoplane microbial community was a mixed community of soil and endosphere microbial communities and that microorganisms can disperse bidirectionally across different compartments of the plant root. On the other hand, in the absence of an enrichment or depletion of core bacterial and fungal OTUs in the rhizosphere, little differences in microbial composition as well as a more shared microbial network structure between the soil and the rhizosphere support the theory that the rhizosphere microbial community is a subset of the soil community. A large number of functional genes (such as nitrogen fixation and nitrite reduction) and more enriched core OTUs as well as a less stable but more complex network structure were observed in the rhizoplane of rubber tree roots. This demonstrated that the rhizoplane is the most active root compartment and a hotspot for plant–soil–environment interactions. In addition, bacterial and fungal communities in the rhizoplane were more stochastic compared to the rhizosphere and soil. Discussion Our study expands our understanding of root-associated microbial community structure and function, which may provide the scientific basis for sustainable agriculture through biological process management.